1995
DOI: 10.1289/ehp.95103366
|View full text |Cite
|
Sign up to set email alerts
|

Dioxin activates HIV-1 gene expression by an oxidative stress pathway requiring a functional cytochrome P450 CYP1A1 enzyme.

Abstract: We have studied the effect of several environmental chemicals on the transient expression of a chloramphenicol acetyltransferase (cat) reporter gene linked to the promoter sequences in the long terminal repeat (LTR) of the human immunodeficiency virus type 1 (HIV-1). Aflatoxin B1, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD; dioxin) and benzo[a]pyrene cause a significant increases in CAT expression in mouse hepatoma Hepa-1 cells. The induction of CAT after TCDD treatment is abolished by administration of N-acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Stimulation of CYP1A and other enzymes can lead to cellular and physiological signs of oxidative stress (Stegeman and Hahn, 1994;Yao et al, 1995) and may contribute to cellular damage and cell death (Kurl et al, 1993;Sakamoto et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of CYP1A and other enzymes can lead to cellular and physiological signs of oxidative stress (Stegeman and Hahn, 1994;Yao et al, 1995) and may contribute to cellular damage and cell death (Kurl et al, 1993;Sakamoto et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…45,46 Moreover, TCDD-induced activation of binding of NF-jB in the LTR of HIV occurs through an AHR-and CYP1A1-dependent oxidative signal. 15 Thus, TCDD-induced, AHR-dependent ROS production, whether via a CYP1, COX2, or some other path, is a potential mechanism for both EZR1 activation and cardiovascular toxicity, although not directly investigated here. 47 This is particularly intriguing in light of findings that induction of a novel LINE-1retrotransposon (L1Md-A2) in mouse vascular smooth muscle cells by benzo[a]pyrene also involves a redoxsensitive mechanism.…”
Section: Ezr1 Induction By Tcddmentioning
confidence: 94%
“…[11][12][13][14] Intriguingly, TCDD has been implicated in stimulating retroviral expression, involving both the AHR and NF-jB. 15 Thus, we investigated the regulation of EZR1, examining the promoter region of EZR1 for possible regulatory elements, including those possibly involved in the induction by TCDD and those that could be involved in retrotransposon regulation. Analysis of the promoter region of the EZR1 retroelement failed to disclose any AHR response elements; however, a putative NF-jB binding site is present.…”
Section: Introductionmentioning
confidence: 99%
“…in monkeys (Riecke et al 2003). Yao et al (1995) found that TCDD can activate expression of human HIV-1 gene expression in vitro by various mechanisms, stressing the importance such compounds may have in the progression of AIDS, and provided data suggesting two different signal transduction pathways.…”
Section: Immune Effectsmentioning
confidence: 99%